PENGARUH TINGKAT KESEHATAN BANK TERHADAP HARGA SAHAM PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nafisah Nurulrahmatiah (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
This research aims to determine the influence of the bank's health level from 2018-2022 in terms of the Risk Profile, Good Corporate Governance, Earnings, Capital aspects on share prices. This research method is to use associative analysis with a quantitative approach. The population of this research are all banks listed on the Indonesia Stock Exchange in 2018-2022. The total sample is 4 banks with the criteria of state-owned banks registered on the IDX. The sampling technique used was purposive sampling. The data collection techniques used are documentation techniques and library techniques. In this research, the data analysis techniques used are classical assumptions, multiple linear regression tests, correlation and determination coefficients, hypothesis testing consisting of the t test and f test with the help of the SPSS version 23 program. The partial test results of this research show that the influence of the bank's health level BUMN during the 2018-2022 period, in terms of Risk Profile, Good Corporate Governance (GCG), and Capital, has a significant influence on share prices. Meanwhile, Earnings have no influence on share prices. And the results of the simultaneous test show that Risk Profile, Good Corporate Governance, Earnings, and Capital together have an influence on stock prices.